An acid-compatible co-polymer for the solubilization of membranes and proteins into lipid bilayer-containing nanoparticles. Issue 22 (30th May 2018) - Hall, Stephen C. L.; Tognoloni, Cecilia; Charlton, Jack; Bragginton, Éilís C.; Rothnie, Alice J.; Sridhar, Pooja; Wheatley, Mark; Knowles, Timothy J.; Arnold, Thomas; Edler, Karen J.; Dafforn, Tim R.
Abstract : Positively charged poly(styrene- co -maleimide) extracts functional membrane proteins into nanodiscs, overcoming some limitations of current nanodisc technology. Abstract : The fundamental importance of membrane proteins in drug discovery has meant that membrane mimetic systems for studying membrane proteins are of increasing interest. One such system has been the amphipathic, negatively charged poly(styrene- co -maleic acid) (SMA) polymer to form "SMA Lipid Particles" (SMALPs) which have been widely adopted to solubilize membrane proteins directly from the cell membrane. However, SMALPs are only soluble under basic conditions and precipitate in the presence of divalent cations required for many downstream applications. Here, we show that the positively charged poly(styrene- co -maleimide) (SMI) forms similar nanoparticles with comparable efficiency to SMA, whilst remaining functional at acidic pH and compatible with high concentrations of divalent cations. We have performed a detailed characterization of the performance of SMI that enables a direct comparison with similar data published for SMA. We also demonstrate that SMI is capable of extracting proteins directly from the cell membrane and can solubilize functional human G-protein coupled receptors (GPCRs) expressed in cultured HEK 293T cells. "SMILPs" thus provide an alternative membrane solubilization method that successfully overcomes some of the limitations of the SMALP method.